A linguagem na definição : transposição didática de conceitos para a formação de auditores internos de gestão da qualidade - Nieto, Florencia del Carmen (My University, 2015)
This research aims to investigate how language can be used in the didactic transposition of the concepts of management system, audit, evidence, requirement, conformity, non-conformity, corrective/preventive action and effectiveness, which are part of the ISO 19011: 2012 standard – Guidelines for auditing management systems, material to be used in the course for auditors of management system. To achieve this objective, we present: the conceptions of knowledge, education, learning and language , based on Morin, Vygotsky, Pozo, Ausubel, Abbagnano and Saussure; the process of the formation of scientific concepts, grounded in Ausubel and Vygotsky; the linguistic/discursive structure of a definition, according to Garcia, Azevedo and Rowell; and the stages of a process of didactic transposition , based on Chevallard and Alvarez. The result is the creation of proposals to define the concepts of auditing in management system. In this regard, for each concept, we executed: (a) an analysis of the linguistic- discursive structure, based on the referred standards; and (b) a proposal for a definition yet to become material to be used in the course for internal auditors of management system, in order to contribute to a more appropriate and effective didactic transposition in this process.
Esta pesquisa propõe-se a investigar como a linguagem pode ser usada na transposição didática dos conceitos de sistema de gestão, auditoria, evidência, requisito, conformidade, não conformidade, ação corretiva/preventiva e eficácia, integrantes da norma NBR ISO 19011:2012 – Diretrizes para auditoria de sistemas de gestão, para o material a ser utilizado no curso de formação de auditores de sistema de gestão (SG). Para atingir o objetivo proposto, apresentam-se: as concepções de conhecimento, educação, aprendizagem e linguagem, com base em Morin, Vygotsky, Pozo, Ausubel, Abbagnano e Saussure; o processo de formação de conceitos científicos, fundamentado em Vygotsky e Ausubel; a estrutura linguísticodiscursiva de uma definição, segundo Garcia, Azevedo e Rowell; e as etapas de um processo de transposição didática, com base em Chevallard e Alvarez. O resultado da pesquisa é a formulação de propostas de definição dos conceitos de auditoria de SG. Nesse sentido, para cada conceito, foram realizadas: (a) uma análise da estrutura linguísitico-discursiva de sua definição na referida norma; e (b) uma proposta de definição que possa constituir-se em material a ser utilizado no curso de formação de auditores internos de sistema de gestão, a fim de contribuir para uma transposição didática mais adequada e eficaz a esse processo.
Keywords: Auditores - Formação; Educação - Linguagem; Auditors - Training of; Education - Language